Preadmission Diet and Zip Code Influences the Pediatric Critical Care Clinical Course for Infants with Severe Respiratory Illness (N = 187) - Leimanis Laurens, Mara L.; Jaji, Amina M.; Montgomery, Jessica; Jess, Jennifer; Ferguson, Karen; Parker, Jessica; Sanfilippo, Dominic; Rajasekaran, Surender (Journal of Pediatric Intensive Care, 2020)
We examined preadmission diet and zip code in infants with severe respiratory illness in the pediatric critical care unit. Patients aged 0 to 5 months admitted to the Helen DeVos Children's Hospital from January 2011 to May 2017 (N = 187), as exclusively formula, exclusively breastfed or mixed diet were included. Formula-fed infants (n = 88; 47%) clustered to zip codes with lower median incomes (<0.005), used public insurance as their payer type (p < 0.005), and were prescribed more ranitidine (p < 0.05) on admission.
Keywords: diet; pediatric critical care unit; severe respiratory illness; median household income; zip code